2022
DOI: 10.1073/pnas.2208040119
|View full text |Cite
|
Sign up to set email alerts
|

Bovine and human endometrium-derived hydrogels support organoid culture from healthy and cancerous tissues

Abstract: Organoid technology has provided unique insights into human organ development, function, and diseases. Patient-derived organoids are increasingly used for drug screening, modeling rare disorders, designing regenerative therapies, and understanding disease pathogenesis. However, the use of Matrigel to grow organoids represents a major challenge in the clinical translation of organoid technology. Matrigel is a poorly defined mixture of extracellular matrix proteins and growth factors extracted from the Engelbret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…Kim et al evaluated the performance of three different hydrogels derived from the small intestine, stomach, and colon, and found that they could support the growth and differentiation of gastrointestinal organoids. 24 Jamaluddin et al investigated the use of bovine and human endometrium-derived hydrogels for organoid culture from healthy and cancerous tissues. 25 Willemse et al developed liver ECM(LECM)-derived hydrogels by decellularising liver tissue to support the growth and differentiation of cholangiocyte organoids.…”
Section: The Challenge To Animal-derived Decellularised Extracellular...mentioning
confidence: 99%
“…Kim et al evaluated the performance of three different hydrogels derived from the small intestine, stomach, and colon, and found that they could support the growth and differentiation of gastrointestinal organoids. 24 Jamaluddin et al investigated the use of bovine and human endometrium-derived hydrogels for organoid culture from healthy and cancerous tissues. 25 Willemse et al developed liver ECM(LECM)-derived hydrogels by decellularising liver tissue to support the growth and differentiation of cholangiocyte organoids.…”
Section: The Challenge To Animal-derived Decellularised Extracellular...mentioning
confidence: 99%
“…After centrifugal cell seeding, each scaffold was capsulated with 0.5% sodium alginate. 13), were cultured in 96-well plates in DMEM/F12 containing 10% FBS, 75 µg/ml streptomycin, 100 IU/ml penicillin and 1% (v/v) amphotericin-b at 37°C in 5% CO2 for 7 days. The medium was changed every two days during the cultural period.…”
Section: Cell Seedingmentioning
confidence: 99%
“…Several cell types are used for the recellularization of endometrial and uterine tissues [5,[10][11][12][13]. In a study by Campo et al in 2017, a mixture of human stromal and epithelial side populations of stem cells was seeded for the decellularized whole pig uterus and the formation of organoid-like structures was proved by their result [11].…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] The results of previous studies have shown that dECMs can facilitate mesenchymal stem cell (MSC) recruitment and differentiation, modulate macrophage polarization, and promote tissue repair without biological toxicity. [13][14][15][16] Although dECM scaffolds derived from cartilage (DCM), bone (DBM), peritoneum, derma, and small intestinal submucosa are used for cartilage tissue restoration after injury, [17][18][19] dECMs originating from different tissues are unlikely to be optimal for regenerating the complex OC region of the joints. This premise has been strengthened by recent evidence suggesting that dECMs derived from a specific region, tissue, or organ can direct the differentiation of progenitor cells toward the phenotype of the corresponding original lineage.…”
Section: Introductionmentioning
confidence: 99%